Effect of closed v. intermittent‐flow respirometry on hypoxia tolerance in the shiner perch Cymatogaster aggregata. Issue 1 (14th January 2016) - Snyder, S.; Nadler, L. E.; Bayley, J. S.; Svendsen, M. B. S.; Johansen, J. L.; Domenici, P.; Steffensen, J. F.
Abstract : This study compares the critical oxygen saturation (O2 crit ) levels of the shiner perch Cymatogaster aggregata obtained using two different methods wherein hypoxia is induced either by the fish's respiration (closed respirometry) or by degassing oxygen with nitrogen (intermittent‐flow respirometry). Fish exhibited loss of equilibrium at a higher O2 saturation in the closed respirometry method when compared with the intermittent‐flow method. Utilization of closed respirometry yielded O2 crit measurements that were almost twice as high as those obtained with intermittent‐flow respirometry. The lower hypoxia tolerance in closed respirometry is consistent with additional stress, caused by a build‐up of ammonia and carbon dioxide and a faster rate in dissolved oxygen decline. The results indicate that these two methods of determining hypoxia tolerance in aquatic organisms are not comparable, and that much care should be given to method choice.